Practitioner Reflections on Engineering Students’ Engagement with e-Learning - Chang, R.; Richardson, J.; Banky, G.; Coller, B.; Lindsay, Euan; Jaksa, M.; Maier, H. (ASEE - American Society for Engineering Education, 2011)
This paper reports on an investigation of student engagement with e-learning, using practitioner reflection as a lens. Five e-learning practitioners each provided a case study from their teaching, which was the focus of practitioners’ reflective accounts. Each of the practitioners had used e-learning as a way of promoting both learning and engagement in their classrooms, and while the contexts in which they worked were varied, there were some emergent similarities in their experiences. The practitioners’ reflections show that e-learning is used as a tool to promote various types of engagement from engineering students; indeed, students’ engagement in some cases evolved beyond that which the practitioners had intended or anticipated. While the intended outcomes were certainly achieved, other emergent changes in student engagement were reported by the practitioners.